Implementasi Aplikasi e-Berpadu (Elektronik Berkas Pidana Terpadu) sebagai Upaya Modernisasi Administrasi Perkara Pidana pada Pengadilan Negeri Denpasar Kelas 1A - Sukma Ayu; I Wayan Suarta; Ratna Artha Windari (Jurnal Ilmu Hukum Sui Generis, 2026)
The modernization of criminal case administration is part of the judiciary’s digital transformation through the Electronic Integrated Criminal Case File (e-Berpadu) application. This study aims to examine the implementation of e-Berpadu in criminal case administration and the utilization of its services at the Denpasar District Court based on Criminal Registry Office data for 2024–2025. This research employed an empirical legal research method with a descriptive qualitative approach. Data were collected through observation, interviews with officials of the Criminal Registry Office, and library research. The findings indicate that e-Berpadu has been effectively implemented since 1 January 2023 through an integrated administrative system supported by document verification, regular monitoring and evaluation, and coordination among law enforcement agencies. The increasing utilization of most e-Berpadu services during 2024–2025 demonstrates its contribution to more effective, efficient, transparent, and accountable criminal case administration.